By the light of the silvery moon : teacher moonlighting and the dark side of teachers' work - Blair, Eleanor (Myers Education Press, LLC, 2018)
Teacher moonlighting has been studied and documented since at least the early 1960s, and yet, it can be easily argued that the phenomenon is still not understood. Teachers moonlight in higher numbers than other professions, and while most teachers claim that they do it for the money, increases in their compensation have not reduced the practice. By the Light of the Silvery Moon is the first book to provide a thorough review of the research on the topic, looking deeply into the intricate workings of a profession that is at least imperiled or, in the best of scenarios, a profession that is in transition. Teachers play a critical role in society, so teaching needs to be a sustainable profession where teachers may still moonlight, but the opportunities to expand the status as well as the content and context of their work are unlimited. This book will fill an important gap in the literature by bringing together the research and situating it within a broader conversation about teachers'work.